Farming the Home Place : a Japanese Community in California, 1919-1982 - Matsumoto, Valerie J. (Cornell University Press, 2019)
In 1919, against a backdrop of a long history of anti-Asian nativism, a handful of Japanese families established Cortez Colony in a bleak pocket of the San Joachin Valley. Valerie Matsumoto chronicles conflicts within the community as well as obstacles from without as the colonists responded to the challenges of settlement, the setbacks of the Great Depression, the hardships of World War II internment, and the opportunities of postwar reconstruction. Tracing the evolution of gender and family roles of members of Cortez as well as their cultural, religious, and educational institutions, she documents the persistence and flexibility of ethnic community and demonstrates its range of meaning from geographic location and web of social relations to state of mind.